“Replacing teachers? Doubt it.” Practitioners' views on adaptive learning technologies' impact on the teaching profession - Merikko, Joonas; Kivimäki, Ville (Frontiers in Education, 2022)
Novel learning technologies have potential in reshaping the teaching profession by automating some parts of the work. However, teachers' perspectives towards automation have generally been critical. In the present study, we examine Finnish education practitioners’ thoughts on adaptive learning technologies and their impact on the teaching profession. Using thematic and epistemic network analysis (ENA), we analyzed 114 social media posts. Supportive posts connected technological capabilities and self-directed or self-regulated learning, emphasizing that technology can also guide and support students. Critical posts connected human presence, educational arrangements, and pupil diversity and equality, emphasizing the importance of teachers’ presence in addressing pupils’ varying needs. Overall, the role of a human teacher was seen as necessary even with adaptive learning technologies available. Our findings reveal themes relevant when discussing the development of adaptive learning technologies and their potential impact on the teaching profession. Moreover, our findings increase the understanding of how supportive and critical argumentation on technology differ.